Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
Let's go through the evaluation of the given expression step by step.
The expression to evaluate is:
[tex]\[ \frac{12 - 3 \gamma}{2} + \nu \left( \frac{2v - 4}{\gamma} \right) \][/tex]
Given:
[tex]\[ \gamma = 3 \][/tex]
Now, let's evaluate each part of the expression:
1. Evaluate the first part: [tex]\(\frac{12 - 3 \gamma}{2}\)[/tex]
Substitute [tex]\(\gamma = 3\)[/tex]:
[tex]\[ 12 - 3 \cdot 3 = 12 - 9 = 3 \][/tex]
Now, divide by 2:
[tex]\[ \frac{3}{2} = 1.5 \][/tex]
So, the first part is [tex]\(1.5\)[/tex].
2. Evaluate the second part: [tex]\(\nu \left( \frac{2v - 4}{\gamma} \right)\)[/tex]
We do not have a given value for [tex]\(\nu\)[/tex] or [tex]\(v\)[/tex] in the problem, so let’s assume the values:
[tex]\[ \nu = 1 \quad \text{and} \quad v = 2 \][/tex]
Substitute [tex]\(v = 2\)[/tex] and [tex]\(\gamma = 3\)[/tex]:
[tex]\[ 2 \cdot 2 - 4 = 4 - 4 = 0 \][/tex]
Now, divide by [tex]\(\gamma\)[/tex]:
[tex]\[ \frac{0}{3} = 0 \][/tex]
Then multiply by [tex]\(\nu\)[/tex] (which is 1):
[tex]\[ 1 \cdot 0 = 0 \][/tex]
So, the second part is [tex]\(0\)[/tex].
3. Sum the two parts:
[tex]\[ 1.5 + 0 = 1.5 \][/tex]
Therefore, the value of the expression [tex]\(\frac{12 - 3 \gamma}{2} + \nu \left( \frac{2v - 4}{\gamma} \right)\)[/tex] for [tex]\(\gamma = 3\)[/tex] is:
[tex]\[ 1.5 \][/tex]
The expression to evaluate is:
[tex]\[ \frac{12 - 3 \gamma}{2} + \nu \left( \frac{2v - 4}{\gamma} \right) \][/tex]
Given:
[tex]\[ \gamma = 3 \][/tex]
Now, let's evaluate each part of the expression:
1. Evaluate the first part: [tex]\(\frac{12 - 3 \gamma}{2}\)[/tex]
Substitute [tex]\(\gamma = 3\)[/tex]:
[tex]\[ 12 - 3 \cdot 3 = 12 - 9 = 3 \][/tex]
Now, divide by 2:
[tex]\[ \frac{3}{2} = 1.5 \][/tex]
So, the first part is [tex]\(1.5\)[/tex].
2. Evaluate the second part: [tex]\(\nu \left( \frac{2v - 4}{\gamma} \right)\)[/tex]
We do not have a given value for [tex]\(\nu\)[/tex] or [tex]\(v\)[/tex] in the problem, so let’s assume the values:
[tex]\[ \nu = 1 \quad \text{and} \quad v = 2 \][/tex]
Substitute [tex]\(v = 2\)[/tex] and [tex]\(\gamma = 3\)[/tex]:
[tex]\[ 2 \cdot 2 - 4 = 4 - 4 = 0 \][/tex]
Now, divide by [tex]\(\gamma\)[/tex]:
[tex]\[ \frac{0}{3} = 0 \][/tex]
Then multiply by [tex]\(\nu\)[/tex] (which is 1):
[tex]\[ 1 \cdot 0 = 0 \][/tex]
So, the second part is [tex]\(0\)[/tex].
3. Sum the two parts:
[tex]\[ 1.5 + 0 = 1.5 \][/tex]
Therefore, the value of the expression [tex]\(\frac{12 - 3 \gamma}{2} + \nu \left( \frac{2v - 4}{\gamma} \right)\)[/tex] for [tex]\(\gamma = 3\)[/tex] is:
[tex]\[ 1.5 \][/tex]
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.